Xenohormesis underlyes the anti-aging and healthy properties of olive polyphenols. (March 2022) - Bucciantini, Monica; Leri, Manuela; Scuto, Maria; Ontario, Marialaura; Trovato Salinaro, Angela; Calabrese, Edward J.; Calabrese, Vittorio; Stefani, Massimo
Highlights: Olive oil polyphenols promote anti-aging and healthy effects within an hormetic dose-response context. Olive oil polyphenols modulate Nrf2-related stress response vitagenes. Olive polyphenols promote lifespan by activation of AMPK pathway and Inhibition of the mTOR pathway. Abstract: The paper provides a comprehensive and foundational mechanistic framework of hormesis that establishes its centrality in medicine and public health. This hormetic framework is applied to the assessment of olive polyphenols with respect to their capacity to slow the onset and reduce the magnitude of a wide range of age-related disorders and neurodegenerative diseases, including Alzheimer's Disease and Parkinson's Disease. It is proposed that olive polyphenol-induced anti-inflammatory protective effects are mediated in large part via the activation of AMPK and the upregulation of Nrf2 pathway. Consistently, herein we also review the importance of the modulation of Nrf2-related stress responsive vitagenes by olive polyphenols, which at low concentration according to the hormesis theory activates this neuroprotective cascade to preserve brain health and its potential use in the prevention and therapy against aging and age-related cognitive disorders in humans.